Antagonistic of Trichoderma spp. as biological control agent against Rhizoctonia solani, Sheath blight disease in rice / Muhammad Ikmal Mohd Zulkifli - Mohd Zulkifli, Muhammad Ikmal (Faculty of Plantation and Agrotechnology, 2019)
Sheath blight caused by Rhizoctonia solani is categorized as the one of the most serious disease that effects the rice production which has widely established in many areas cultivation rice in Malaysia. The effective of Trichoderma was tested towards inoculated rice with R. solani which is the causal agent of disease severity. Therefore, the objectives of this study were to conduct pathogenicity test of R. solani of sheath blight disease on rice and to determine the performance of Trichoderma spp. for measurement against R. solani. Rice was growth under normal condition until reach maximum tillering and was conducted to pathogenicity test by using conidial suspension method. After that, suspension of Trichoderma was used as biological control agent. Disease severity was observed and recorded for 6 days in order to observe the difference of application using Trichoderma spp. All five isolates showed the disease severity after six days of inoculation with isolate SB 01 and SB 04 has 95% and 90% which is the highest score. Meanwhile, after the application of Trichoderma, isolate SB 01 and SB 04 has 50% and 30% score which is the highest score. As conclusion, by using Trichoderma spp. as biological control can be decreased the disease severity of sheath blight disease which causes by Rhizoctonia solani as pathogenic agent.